A MARKET RESEARCH ON THE FISH FARMING INDUSTRY IN THE REPUBLIC OF KARELIA, LENINGRAD OBLAST, AND MURMANSK OBLAST - Vakhrusheva, Anastasiia (Karelia-ammattikorkeakoulu (Pohjois-Karjalan ammattikorkeakoulu), 2015)
The aim of the report is to investigate three Russian fish farming markets: the Republic of Karelia, Leningrad Oblast, and Murmansk Oblast. The main goal is to analyze the current market situation and find potential customers and partners for the company Savon Taimen Oy and its subsidiaries. The research is conducted by using secondary and collecting primary data via several methods: questionnaires, personal calls, e-mails and interviews with experts from the fishing field. Afterwards, information was analyzed to prepare conclusions and recommendations for further actions. Nowadays, the border is opened for rainbow trout fingerlings. More importantly they are in demand and Russian companies are purchasing it from abroad. Therefore, company should conduct work to attract potential customers by presenting its offers via e-mail and providing flexible payment methods.